Faraday rotation in CMB maps. Issue Volume 11:Issue S308(2015) (12th October 2016) - Ruiz-Granados, Beatriz; Battaner, Eduardo; Florido, Estrella
Abstract: WMAP CMB polarization maps have been used to detect a low signal of Faraday Rotation (FR). If this detection is not interpreted as simple noise, it could be produced: at the last scattering surface (LSS) (z=1100), being primordial, at Reionization (z=10), in the Milky Way. The second interpretation is favoured here. In this case magnetic fields at Reionization with peak values of the order of 10 -8 G should produce this observational FR.